Managing Dynamic Context to Optimize Smart Interactions and Services (2010)
With the rapid growth of socio-technical ecosystems, smart interactions and services are permeating every walk of life. As smart interactions must managed automatically and interactively in response to evolving user's matters of concern, the smart Internet requires creative approaches where services and interactions are implemented with awareness of, and dynamic adaptation to, users, computational environments, changing policies and unknown requirements. Consequently, modeling and managing dynamic context is critical for implementing smart services and smart interactions effectively. Thus, smart interactions need infrastructure to acquire, compose, and distribute context information to multiple execution endpoints. Moreover, context management must be controlled and governed to optimize system properties. This chapter surveys context modeling and management approaches intended for the optimization of smart interactions and services, discusses the main challenges and requirements of context-awareness in the smart Internet, and provides a feature-based framework useful for the evaluation and implementation of context modeling and management mechanisms. © 2010 Springer-Verlag Berlin Heidelberg.